2018
DOI: 10.1039/c8cp05148h
|View full text |Cite
|
Sign up to set email alerts
|

Using microgels to control the morphology and optoelectronic properties of hybrid organic–inorganic perovskite films

Abstract: Spin coating mixed microgel/perovskite precursor solutions gives disordered inverse opal perovskite films with morphologies and optoelectronic properties that are controlled by the microgel particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 59 publications
2
23
1
Order By: Relevance
“…121,122 However, the thermal stability can be increased by fully replacing iodide with bromide. 123,124 In fact, CsPbBr 3 is stable till 580 1C 125 and presents great charge transport ability and mean free path. 126 This perovskite was used in planar PSCs and showed a remarkable stability for more than three months in humid air.…”
Section: High-temperature Processed Front Electrodesmentioning
confidence: 99%
“…121,122 However, the thermal stability can be increased by fully replacing iodide with bromide. 123,124 In fact, CsPbBr 3 is stable till 580 1C 125 and presents great charge transport ability and mean free path. 126 This perovskite was used in planar PSCs and showed a remarkable stability for more than three months in humid air.…”
Section: High-temperature Processed Front Electrodesmentioning
confidence: 99%
“…Nowadays, these polymeric systems have attracted considerable attention in a large number of scientific and technological fields, such as nanotechnology, materials science, life sciences, and medicine . They have been applied in surface coating, drug accumulation and release, drug delivery, optoelectronic switches, and many other applications. Among them, stimuli-responsive (smart) nanogels (gels with dimensions in the nanometer range) undergo a sharp and reversible volume phase transition (a conformational change that leads to a drastic variation in the degree of swelling) in a response to environmental stimuli, such as the change in temperature, pH, ionic strength, or solvent nature .…”
mentioning
confidence: 99%
“…In the earlier study, the MGs had a diameter of 913 nm and were deposited on the substrate causing the perovskite to crystallize in the inter-MG spaces. 35 We subsequently decreased the MG diameter to 336 nm and reported that that these smaller MGs were encapsulated within the perovskite matrix if the film thickness was larger than the MG diameter. 36 Here, we use much smaller NGs with a diameter of 40 nm.…”
Section: Introductionmentioning
confidence: 99%